Off-Axis Properties of Cross-Ply Metal Matrix Composites at Quasi-Static and High Strain Rates - Hall, Ian W.; Taşdemirci, Alper; Taşdemirci, Alper; Kara, Ali; Kara, Ali (Elsevier Ltd., 2011)
Cylindrical samples of a 0/90° cross-ply Nextel 610™/A1-6061 (∼55Vf%) metal matrix composite have been subjected to compression testing at quasi-static and high strain rates over a range of angles between 0° and ±45° with respect to the principal fiber directions. The results, combined with testing in the longitudinal, transverse and through thickness directions, provide a detailed description of the response of such composites over a wide range of orientations. In addition, metallographic and fractographic studies along with high-speed camera records provide detailed information about the sequence of deformation events leading to fracture. Results confirm not only the strong dependence of mechanical properties upon orientation but also the critical importance of precise fiber alignment and processing in obtaining the desired theoretical properties. A misalignment of 10° was sufficient to cause an -40% decrease in maximum stress and the properties were found to vary by >70% over the orientations investigated. The high strain rate properties were generally significantly greater than those measured quasi-statically. A numerical model based on the commercial explicit finite element code LS-DYNA was used to investigate the compressive deformation and fracture of the composite. Experimental results are compared with those of the numerical model. © 2011 Published by Elsevier Ltd.
11th International Conference on the Mechanical Behavior of Materials, ICM11; Como; Italy; 5 June 2011 through 9 June 2011
Keywords: Strain rate; Off-axis properties; Metal matrix composite; Compression